ANALISIS KONSUMSI BBM MOTOR DIESEL PADA UJI REM DENGAN DAYA 7.5 & 8 HP - Muchlisinalahuddin Muchlisinalahuddin; Rudi Kurniawan Arief; Joko Pitoyo (Rang Teknik Journal, 2022)
The choice of a diesel-fueled engine is often a problem among the public because there are often complaints that the old diesel-fueled motors are too wasteful with low house power, and it is often doubtful when buying a new engine with high house power, increasing fuel consumption. large, therefore we carry out testing to eliminate doubts in the community in order to get specifications that are in accordance with good power or power but efficient fuel consumption, therefore to get real and real evidence in the selection it is necessary to test 2 engine units with different house power, different types, and different production times, therefore a test of fuel consumption against time, load against time is carried out, using a 7.5 HP diesel engine with 8 HP provided that this 7.5 HP engine is an old engine and the 8 HP engine is a new engine, after By experimenting with fuel comparisons, it was found that the new engine with a larger house power capacity was in fact more efficient in fuel consumption than the old engine with a capacity of 7.5 HP with an average ratio of about 18.49%.